GREEN HUMAN RESOURCE MANAGEMENT PRACTICES AND THE ROLE OF THE MINISTRY OF CLIMATE CHANGE AND ENVIRONMENTAL COORDINATION, PAKISTAN: A QUALITATIVE DOCUMENT ANALYSIS - Dr. Asmat Nawaz Khattak; Farooq Amjid; Ahmad Waqas (International Journal of Contemporary Issues in Social Sciences, 2024)
“Green HRM” is a revolutionary and strategic approach to managing human resources. Organizations are becoming more attractive to both domestic and global consumers when they use green HRM practices. Global as well as local institutions strongly support green HRM practices in order to preserve the environment for coming generations. We evaluated the strategic and regulatory role of Pakistan's The Ministry of Climate Change and Environmental Coordination to guide the policy makers, students and other interest groups. We conducted document analysis and collected the qualitative data from on line websites. We also conducted thematic analysis to identify relevant themes within the data. We came to a number of noteworthy conclusions. We found that in order to promote green behavior, green employees, and green organizations, organizations need to adopt environmental strategy. Without the support of upper management, goals might not be accomplished. To promote green behavior and a green organization, organizations coordinate and integrate their HR and environmental strategies. Green behaviour of employees is needed to implement the NEQS standards. Additionally, to improve the sustainability of the company, a consistent green HRM strategy must be developed.